Modern view of the classification, diagnostic and clinical manifestations of periodontitis in children and adolescents - Khomenko Лариса Олександрівна; Ostapko Олена Іванівна; Bidenko Наталія Василівна; Golubeva Інна Миколаївна (Actual Dentistry, 2023)
Summary. In the article the modern international classification of periodontal diseases is considered. The expediency of it use in the practice of pediatric therapeutic dentistry is justified. Emphasized that every child needs early diagnostic of periodontal tissue status by periodontal probing and detection of bleeding during probing as the main clinical symptom of pathological process. The clinical and rentgenological manifestations of different forms of periodontitis, include associated with somatic diseases, are presented.